2020
DOI: 10.3390/v12020171
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Risk of Human Herpesvirus 6 and Cytomegalovirus Transmission to Ugandan Infants from Viral Shedding in Saliva by Household Contacts

Abstract: Human herpesvirus 6 (HHV-6) and cytomegalovirus (CMV) infections are common in early childhood. In a prospective Ugandan birth cohort study, most infants acquired HHV-6 (24/31; 77%) and CMV (20/30; 67%) during follow-up. To assess the transmission risk, we modeled a dose–response relationship between infant HHV-6 and CMV infections and weekly oral viral shedding by mothers and all other (“secondary”) children in the home. Oral viral loads that were shed by mothers and secondary children were significantly asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
1
17
0
3
Order By: Relevance
“…Our prior work strongly suggests the presence of a transmission dose response curve in which exposure viral load is a key determinant of transmission risk 39 , 40 . Our current analysis is built upon this assumption.…”
Section: Discussionmentioning
confidence: 78%
“…Our prior work strongly suggests the presence of a transmission dose response curve in which exposure viral load is a key determinant of transmission risk 39 , 40 . Our current analysis is built upon this assumption.…”
Section: Discussionmentioning
confidence: 78%
“…For influenza, the dose of viral exposure is related to the probability of infection in human challenge studies ( Memoli et al, 2015 ) and early antiviral treatment reduces household transmission ( Pebody et al, 2011 ; Goldstein et al, 2010 ). Household shedding of human herpesvirus-6 is closely linked to subsequent infection in newborns ( Mayer et al, 2020 ) and infants shedding high levels of cytomegalovirus in the oropharynx predictably transmit the virus back to their mothers ( Boucoiran et al, 2018 ). Studies in mice definitively demonstrated that viral exposure dose determines likelihood of SARS-CoV-1 infection, ( Watanabe et al, 2010 ) and SARS-CoV-2 experiments in golden hamsters are also highly suggestive of dose-dependent infection ( Sia et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For influenza, the dose of viral exposure is related to the probability of infection in human challenge studies, 14 and early treatment reduces household transmission. 15 , 16 Household shedding of human herpesvirus-6 is closely linked to subsequent infection in newborns, 17 and infants shedding high levels of cytomegalovirus in the oropharynx predictably transmit the virus back to their mothers. 18 …”
Section: Introductionmentioning
confidence: 99%